A case of recurrent aerococcus urinae infective endocarditis with associated cerebral embolic phenomena. Issue 2 (28th February 2020) - Ravji, Pooja; Brown, Nicholas
Abstract : Aerococcus urinae is a gram positive, alpha haemolytic cocci that rarely is associated with urinary tract infections, bacteraemia and infective endocarditis. We describe a case of recurrent aerococcus urinae endocarditis with associated cerebral embolic phenomena. A 76 year old man presented with sudden onset right sided weakness and dysphasia. CT and MRI head imaging showed infarcts in the left pons and cerebellum suspicious of embolic aetiology. He had a background of a prosthetic mitral valve replacement following an episode of culture negative infective endocarditis associated with discitis and a psoas abscess 3 years previously. A 16S rRNA PCR on valve tissue had yielded an aerococcus urinae. The anaerobic bottle of a blood culture taken on his present admission flagged positive at 48 hours but no organisms were seen on gram stain. However, Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI – TOF MS) identified an aerococcus urinae 4 hours later. The same organism was also identified in the aerobic bottle which had flagged positive later the same day with gram positive cocci in clusters. Susceptibility testing revealed a MIC (Minimum Inhibitory Concentration) of 0.032, 1 and 8mg/L for penicillin, vancomycin and gentamicin respectively. A transthoracic echocardiogram confirmed reoccurrence of endocarditis with a 1.5cm lesion on the mitral valve. There was no evidence of other embolic phenomena. The patient was managed medically with initial treatment with intravenous vancomycin and gentamicin followed by benzylpenicillin and gentamicin for 6 weeks. The patient made slow rehabilitative progress and remained debilitated by his right sided hemiparesis.